Observation of orbitally excited Bs mesons - Aaltonen, T; Abulencia, A; Adelman, J; Akimoto, T; Albrow, MG; González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; et al. (2008)
We report the observation of two narrow resonances consistent with states of orbitally excited (L=1) Bs mesons using 1fb-1 of pp̄ collisions at s=1.96TeV collected with the Collider Detector at Fermilab II detector at the Fermilab Tevatron. We use two-body decays into K- and B+ mesons reconstructed as B+→J/ψK+, J/ψ→μ+μ- or B+→D̄0π+, D̄0→K+π-. We deduce the masses of the two states to be m(Bs1)=5829.4±0.7MeV/c2 and m(Bs2*)=5839.6±0.7MeV/c2. © 2008 The American Physical Society.